2016
DOI: 10.5565/rev/athenea.1478
|View full text |Cite
|
Sign up to set email alerts
|

The Child’s Body as a Disorder: discursive approaches towards ADHD

Abstract: El Trastorno de Déficit Atencional con Hiperactividad (TDAH) es el diagnóstico neurológico más frecuente en niños en edad escolar atendidos en el servicio de atención primaria en Chile. Se han implementado nuevas regulaciones que definen cuáles profesionales pueden diagnosticar y tratar el trastorno. En este estudio nos aproximamos a la construcción del TDAH desde una perspectiva discursiva, a través del análisis de entrevistas a padres, profesionales de las áreas de la salud y educación encargados del abordaj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…ADHD is defined as a chronic disorder characterized by difficulty paying attention and controlling impulses. Qualitative studies in Chile have revealed difficulties in following a model of psychosocial diagnosis of ADHD and that many students with a diagnosis of ADHD receive medication, implying the emergence of new discourses of medicalization for children who are deemed to be ‘difficult to educate and with problems in school processes’ (Ceardi et al, 2016). A similar situation has occurred in the United States, where the Centers for Disease Control and Prevention (2014) reported that 2.9 million children are being medicated in conjunction with an emotional disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…ADHD is defined as a chronic disorder characterized by difficulty paying attention and controlling impulses. Qualitative studies in Chile have revealed difficulties in following a model of psychosocial diagnosis of ADHD and that many students with a diagnosis of ADHD receive medication, implying the emergence of new discourses of medicalization for children who are deemed to be ‘difficult to educate and with problems in school processes’ (Ceardi et al, 2016). A similar situation has occurred in the United States, where the Centers for Disease Control and Prevention (2014) reported that 2.9 million children are being medicated in conjunction with an emotional disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Así, se han instaurado organismos fiscalizadores de la normativa educacional, nuevas funciones de vigilancia del quehacer de las escuelas, y nuevos mecanismos para la participación de los agentes escolares, que ahora tendrían la posibilidad explícita de denunciar frente a problemas educacionales (CARRASCO et al, 2018). Estos mecanismos han sido aceptados como una justificación discursiva para comprender los problemas educacionales (SAAVEDRA;VILLALTA, 2007;MUÑOZ et al, 2014), sobre todo para aquellos vinculados a la regulación conductual de los estudiantes disruptivos (FOLADORI;SILVA, 2014;CEARDI et al, 2016), y los problemas convivenciales entre los miembros de la comunidad escolar (LÓPEZ et al, 2011;ASCORRA et al, 2018).…”
Section: El Discurso De Judicialización Y Las Denuncias Escolaresunclassified